ARABIC LANGUAGE: SOCIAL POWER AND LINGUISTIC STABILITY - Ahmed Tidjai Sikebir (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This study examines the status of the Arabic language as an effective social force and a fundamental factor in achieving linguistic stability across centuries. It highlights the role of Arabic in shaping the cultural and civilizational identity of Arabic-speaking societies, strengthening social cohesion, and transmitting values and knowledge across generations. The study also discusses the manifestations of linguistic stability in Arabic and the reasons for its continuity and ability to adapt to contemporary social and technological transformations while preserving its core structure and distinctive features. It concludes that the social power of the Arabic language has played a major role in protecting it from decline, making it a living language capable of keeping pace with modern developments while maintaining its authenticity.